IMPACT EVALUATION OF DENGUE HEMORRHAGIC FEVER CONTROL PROGRAM IN TEMBALANG DISTRICT, SEMARANG CITY - Wibowo, Rizky Arvianto; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2019)
The dengue hemorrhagic fever control program (DBD) in Tembalang District, Semarang City is constrained by the lack of public awareness in conducting dengue fever control programs (DHF) such as eradicating mosquito nests (PSN) and routine larvae checks (PJR). This study aims to determine the impact of dengue hemorrhagic fever control programs (DHF) and the obstacles faced. The method used is a qualitative method with data collection techniques of observation, interviews, and documentation. Determination of the subject using purposive sampling technique, the validity of the data using data triangulation techniques. The results showed that RW 2, Rowosari and RW 7, Sendangguwo, in 2019, were the highest cases of dengue hemorrhagic fever (DBD). However, RW 7 in Sendangguwo Urban Village is faster in handling dengue hemorrhagic fever (DHF) cases, shown by the community who are diligent in conducting PSN, routine larvae checks (PJR) are carried out every week at each homestead (Dawis), increase in larval free rate (ABJ). The problem is the lack of health surveillance personnel (gasurkes), the community does not yet have the awareness to conduct PSN, there is no routine schedule of routine larvae inspection (PJR) activities in the community, the low rate of larval free (ABJ). Suggestions to increase the number of health surveillance personnel (gasurkes), increase public awareness to carry out dengue fever control programs (DHF), increase the routine of the community doing routine larvae (PJR) activities once a week.